Adsorption and kinetics of elemental mercury vapor on activated carbons impregnated with potassium iodide, hydrogen chloride, and sulfur - Jang, Ha-Na; Back, Seung-Ki; Sung, Jin-Ho; Jeong, Bup-Mook; Kang, Youn-Suk; Lee, Chul-Kyu; Jurng, Jongsoo; Seo, Yong-Chil (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2017)
Coal combustion emits large amounts of elemental mercury that cannot be captured by air pollution control devices such as flue gas desulfurization because of its insolubility. Therefore, technological advances are necessary for capturing elemental mercury. We conducted various tests on adsorption of elemental mercury using KI-, HCl-, and S-impregnated activated carbons, which were compared with virgin activated carbon. Tests with virgin activated carbon revealed that the optimal adsorption temperature for capturing elemental mercury was 363 K. The adsorption efficiency for elemental mercury was nearly 100% using activated carbon impregnated with 1% and 5% KI and 1%, 5%, and 10% HCl. Through kinetic analyses of the impregnated activated carbons, the optimal equilibrium adsorption capacities of KI-, HCl-, and S-impregnated activated carbons for mercury were determined to be 333.3, 333.3, and 256.4mg/g, respectively, by using a pseudo second-order kinetic model.
Keywords: METHYLENE-BLUE; REMOVAL; GAS